DIAGNOSTICS AND SURGICAL TREATMENT OF LUNG CANCER IN CONDITIONS OF SPECIAL THORACAL DEPARTMENT FOR PATIENTS WITH PURULENT LUNG DISEASES - I. V. Deinega; V. I. Egorov; P. M. Ionov; A. L. Akopov (Вестник хирургии имени И.И. Грекова)
The authors investigated features of diagnostics and surgical treatment of lung cancer which was complicated by purulent destructive process. The possibilities of radical operative intervention were considered after preliminary adequate treatment of purulent complications in 226 patients. It was noted, that the diagnostic thoracotomy should be used in doubtful cases in order to estimate the resectability of lung cancer.